Impact of Solanum Torvum Rootstocks on Grafted and Non-Grafted Tomato (Lycopersicon esculentum Mill.) Cultivars - Nepal, Susima; Shrestha, Punam; Bhattarai, Choodamani; Chaulagain, Bidur P. (Nepalese Journal of Agricultural Sciences, 2025)
This study evaluated the growth, yield, and fruit quality of grafted and non-grafted tomato (Lycopersicon esculentum Mill.) cultivars under protected cultivation. Conducted from March to July 2024 at Bhattarai Shiva Shakti Krishi Farm, Bhaktapur, Nepal, the experiment used two cultivars, Heemsikhar and Srijana, as scions grafted onto Solanum torvum (wild brinjal) rootstock. Four treatments— T1: Grafted Heemsikhar, T2: Control Heemsikhar, T3: Grafted Srijana, and T4: Control Srijana—were put in a randomized complete block design with five replications. Key parameters, including plant growth, fruit yield, and quality traits such as firmness, total soluble solids (TSS), titratable acidity (TA), sugar-acid ratio, and vitamin C content, were assessed. Grafting significantly improved fruit yield, TA, and vitamin C content but had no effect on plant height, stem diameter, fruit firmness, TSS, or sugar-acid ratio. The T3 (Grafted Srijana) treatment yielded the highest fruit weight, with 129.60 g/plant in the first harvest and 121.30 g/plant in the second. T1 (Grafted Heemsikhar) followed, with yields of 112.01 g/plant and 84.60 g/plant at the respective harvests. T3 also recorded the highest TA and vitamin C content, highlighting its potential for enhancing both yield and nutritional quality. These findings provide valuable insights for optimizing tomato cultivation through grafting and offer practical recommendations for improving productivity and fruit quality under protected conditions.